Emergency Preparation and Uncertainty Persistence - Sundaresan, Savitar (Management Science, 2024)
Unusual events trigger persistent spikes in uncertainty. Standard models cannot match these dynamic patterns. This paper presents a unified framework, motivated by the literature on inattention. Agents choose whether and how to prepare for different possible states of the world by collecting information. Agents optimally ignore sufficiently unlikely events, so the occurrence of such events does not resolve, but rather increases, uncertainty. Uncertain agents have dispersed beliefs, making it harder to focus future preparation. Thus, uncertainty begets uncertainty for an inattentive agent, endogenously persisting. In a financial application, this framework matches patterns in volatility, volume of trade, belief dispersion, and spreads. This paper was accepted by Victoria Ivashina, finance. Supplemental Material: The data file is available at https://doi.org/10.1287/mnsc.2023.4836 .